2007
DOI: 10.1016/j.yjmcc.2007.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Vascular response to intra-arterial injury in the thrombospondin-1 null mouse

Abstract: Thrombospondin-1 (TSP-1) is a multifunctional, extracellular matrix protein that has been implicated in the regulation of smooth muscle cell proliferation, migration and differentiation during vascular development and injury. Vascular injury in wildtype and TSP-1 null mice was carried out by insertion of a straight spring guidewire into the femoral artery via a muscular arterial branch. Blood flow was restored after the muscular branch was ligated. The injury completely denuded the endothelium and caused media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…4,14 The role of endogenous TSP1 in the process of thrombus formation is less clear in severe vessel injury such as those created by guide wire endothelial stripping of arterial segments. 64 Consistent with previous reports that CD47-binding peptides increase platelet aggregation, 10-12 we found that CD47-binding peptides potently antagonize NO-stimulated delays in aggregation. This occurred under high shear and static conditions.…”
supporting
confidence: 93%
“…4,14 The role of endogenous TSP1 in the process of thrombus formation is less clear in severe vessel injury such as those created by guide wire endothelial stripping of arterial segments. 64 Consistent with previous reports that CD47-binding peptides increase platelet aggregation, 10-12 we found that CD47-binding peptides potently antagonize NO-stimulated delays in aggregation. This occurred under high shear and static conditions.…”
supporting
confidence: 93%
“…and is frequently expressed at sites of inflammation and wound healing [14] . In vitro studies have demonstrated that TSP-1 is associated with atherosclerotic lesions, occluded grafts and vascular smooth muscle cell hyperplasia after vascular injury [15] . TSP-1 was also reported to be important in modulating fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…TSP-1 is a multifunctional glycoprotein expressed by a variety of cell types, such as platelets, vascular smooth muscle cells, endothelial cells and fibroblasts [14] . Some researches have previously determined that increases in TSP-1 expression could exacerbate vascular injury [15] and fibrotic complications involving the myocardium and mesangial cells [16,17] .…”
mentioning
confidence: 99%
“…Neointima formation following carotid artery ligation is reduced in TSP1 null mice, with decreased α-SMA-positive cells, but increased collagen and osteopontin deposition [57]. Others observed no difference in vascular response to wire-induced injury between wild-type and TSP1 null mice, but more thrombus formation [58]. Because TSP1 has multiple functions apart from regulation of TGF-β activation, including regulating MMP activity and NO signaling, these null phenotypes might reflect the absence of multiple, sometimes contradictory functions.…”
Section: Discussionmentioning
confidence: 99%